Analysis of The Drivers of Consumer Purchasing Decisions in The Digital Era: The Role of Social Media Marketing, E-Service Quality, and Payment Safety - Uce Karna Suganda; Isti Arrifianti (PT Mattawang Mediatama Solution, 2023)
The objective of this study is to examine and analyze the influence of consumer purchasing decisions in digital era by considering the influence of social media marketing, e-service quality, and payment safety. The respondents are 120 university students in Bandung, West Java who use digital platform to purchase products or services. The data is collected by distributing questionnaires to the respondents, and analyzed using the multiple regression analysis with SPSS 26. The findings of this study indicate that consumer purchasing decision is positively and significantly influenced by social media marketing, e-service quality, and payment safety. This means that the owners or managers of products and services sold through online platforms must pay attention to these three aspects, as it will increase the consumer purchase decisions, thus enhancing the company’s profitability.